(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background: Abdominoplasty or Abdominoplastie (in French), commonly referred to as "tummy Tuck," is a procedure for reducing excess skin and fat around the abdomen and strengthening the muscles of the abdominal wall. Several studies have suggested that drainless abdominoplasty using PTS shows a high potential for reducing the risk of seroma formation. Objective: The aim of this research is to assess the following consequences and complications of abdominoplasty using progressive tension suture and abdominoplasty without using PTS. Materials and Methods: After taking informed consent from patients to take part in the study, surgical procedure was performed for patients under general anesthesia and with traditional abdominoplasty technique. Patients are randomly divided into two groups: group A: abdominoplasty with PTS, Group B: patients who had abdominoplasty without PTS. The following variables examined the duration of surgery, the assessment of pain, daily and total drainage through the drain, drain removal timing hospitalization, local and systemic complications (delayed wound healing, infection, thrombotic accidents seroma occurrences (including frequency and drained volumes), readmissions, and emergency visits. The Numeric Rating Scale (NRS) was utilized to gauge pain intensity, with subsequent data entry and statistical analysis performed using SPSS Version 26. Results: The study included 24 women, the age of patients in the sample ranged between 31-60 years with an average about 40.5 years. The average value of BMI was 29.4 kg/m2. The surgery took 130.1 minutes on average (94-160 minutes). The average degree of pain was 5.04, the average daily drainage through study patients was 62.15 ml. Seroma formations were reported in one and three patients in Groups A and B, respectively, with varying drainage frequencies and volumes. Scar of surgical procedure were faster to heal in group "A" in which PTS were used compared to group "B" in which it didn’t. Conclusions: Progressive Tension Sutures to reduce the risk of seroma, reduce daily and total drainage, periodic follow-up of patients in case of seroma formation, more studies involving larger numbers of patients and a longer period of study, are needed.